TRAINING AND DEVELOPMENT, KNOWLEDGE SHARING, AND INNOVATIVE WORK BEHAVIOR AMONG SELLING EMPLOYEES IN A MANUFACTURING COMPANY - Yasyfa Maghfyra; Sri Raharso (Fakultas Ekonomi, 2026)
Employee innovation has become increasingly important for manufacturing companies seeking to remain competitive in rapidly changing business environments. This challenge is particularly relevant for selling employees, whose direct interactions with customers provide valuable market knowledge that can stimulate innovation. This study examines the effects of training and development and knowledge sharing on innovative work behavior among selling employees at PT X. A quantitative research design was adopted using a census of 171 selling employees. Data were gathered through a five-point Likert questionnaire and analyzed using multiple linear regression. The findings reveal that both training and development and knowledge sharing positively and significantly influence innovative work behavior. Among the two predictors, knowledge sharing demonstrates the stronger contribution, indicating that continuous exchange of knowledge and experience plays a more prominent role in encouraging innovative behavior than formal competency development alone. The regression model also confirms that the two variables jointly explain a substantial proportion of the variance in innovative work behavior. These results highlight the importance of integrating structured employee development with an organizational climate that encourages continuous knowledge exchange. This study extends the literature by providing evidence from selling employees in Indonesia's manufacturing sector and emphasizes that combining competency development with knowledge-sharing practices can strengthen employees' innovative work behavior.